2011
DOI: 10.1103/physrevlett.106.068301
|View full text |Cite
|
Sign up to set email alerts
|

How Topological Rearrangements and Liquid Fraction Control Liquid Foam Stability

Abstract: The stability of foam is investigated experimentally through coalescence events. Instability (coalescence) occurs when the system is submitted to external perturbations (T1) and when the liquid amount in the film network is below a critical value. Microscopically, transient thick films are observed during film rearrangements. Film rupture, with coalescence and eventual collapse of the foam, occurs when the available local liquid amount is too small for transient films to be formed. Similar experiments and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 22 publications
3
95
0
Order By: Relevance
“…The film thickness decreases when the elongational modulus of the interface decreases, which compares favourably with experiments made in a steady regime (Cohen-Addad & di Meglio 1994;Lal & di Meglio 1994;Saulnier et al 2011). Film extraction from menisci also occurs in foams (Biance, Delbos & Pitois 2011;Seiwert et al 2013) and plays an important role in foam rheology and stability. Additional studies are required to determine if, in a three-dimensional foam, such film formation can be considered to occur in a quasi-steady regime, in which case our study would be relevant to this topic.…”
Section: Resultssupporting
confidence: 75%
“…The film thickness decreases when the elongational modulus of the interface decreases, which compares favourably with experiments made in a steady regime (Cohen-Addad & di Meglio 1994;Lal & di Meglio 1994;Saulnier et al 2011). Film extraction from menisci also occurs in foams (Biance, Delbos & Pitois 2011;Seiwert et al 2013) and plays an important role in foam rheology and stability. Additional studies are required to determine if, in a three-dimensional foam, such film formation can be considered to occur in a quasi-steady regime, in which case our study would be relevant to this topic.…”
Section: Resultssupporting
confidence: 75%
“…It corresponds to k = 0. This process of film pulling from the Plateau border is sketched in figure 4(a), and has been proposed before (Buzza et al 1995;Biance et al 2011;Seiwert et al 2013). It corresponds fairly to the case experimentally observed in figure 3d, with k = 0.1.…”
Section: Resultssupporting
confidence: 60%
“…By numerically solving unsteady thin film equation, the film profile can be recovered and therefore the surface viscosity of the interfaces can be deduced. These results underly that a general mode of dissipation during a T1 process is not valid, and are a new starting point for T1 dynamic studies in these various cases, as well as for defining conditions for film rupture during these dynamical events (Carrier & Colin 2003;Biance et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] Mathematical model shows that the gravity drainage speed is proportional to square of mean cell diameter D m 2 , so liquid drainage of foams under high pressure is significantly slowed down by the obvious decrease in mean cell size. In recent studies, it is shown that break of liquid films during structure rearrangement is related to the liquid ratio of foams, [31] so the delay in gravity drainage also leads to a slow cell size coarsening.…”
Section: Density-structure Correlationmentioning
confidence: 99%